# 1/(x-3)-4/x-3-5=0

## Simple and best practice solution for 1/(x-3)-4/x-3-5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 1/(x-3)-4/x-3-5=0 equation:

1/(x-3)-4/x-3-5=0

Domain of the equation: (x-3)!=0
We move all terms containing x to the left, all other terms to the right
x!=3
x∈R

Domain of the equation: x!=0
x∈R

We add all the numbers together, and all the variables
1/(x-3)-4/x-8=0
We calculate fractions

x/(x^2-3x)+(-4x+12)/(x^2-3x)-8=0
We multiply all the terms by the denominator

x+(-4x+12)-8*(x^2-3x)=0
We multiply parentheses
-8x^2+x+(-4x+12)+24x=0
We get rid of parentheses
-8x^2+x-4x+24x+12=0
We add all the numbers together, and all the variables
-8x^2+21x+12=0
a = -8; b = 21; c = +12;Δ = b2-4acΔ = 212-4·(-8)·12Δ = 825The delta value is higher than zero, so the equation has two solutionsWe use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$The end solution:
$\sqrt{\Delta}=\sqrt{825}=\sqrt{25*33}=\sqrt{25}*\sqrt{33}=5\sqrt{33}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(21)-5\sqrt{33}}{2*-8}=\frac{-21-5\sqrt{33}}{-16}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(21)+5\sqrt{33}}{2*-8}=\frac{-21+5\sqrt{33}}{-16}$

`